The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1988
DOI: 10.1113/jphysiol.1988.sp017025
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and parotid gland function in the rat.

Abstract: SUMMARY1. We previously reported that parotid gland secretion is decreased in rats deprived of vitamin D (Glijer, Peterfy & Tenenhouse, 1985). In the present study we examine whether this effect is a direct result of the absence of vitamin D or due to the secondary systemic effects of vitamin D deficiency.2. Offspring of rats maintained on a calcium-supplemented (1-2%), vitamin-Ddeficient diet were weaned onto the same diet and examined after 8 weeks. Using this method it was possible to maintain serum calcium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Several animal studies have demonstrated that vitamin D receptors are present in the parotid, submandibular and sublingual salivary glands, which suggest a possible role for vitamin D in the regulation of salivary secretion. This is supported by the finding that salivary flow rates were stimulated after treatment with vitamin D 3 in vitamin D-deficient rats (Peterfy, Tenenhouse, & Yu, 1988;Stumpf, 2008). Although the influence of vitamin D on salivary flow rate has not yet been demonstrated in humans, the finding that there was a significant positive correlation between plasma total 25(OH)D concentration and salivary flow rate in the endurance athlete cohort (N = 225) (unpublished data in our previous study (He et al, 2013), r = 0.196, P = 0.003; Pearson correlation test) might lend some support to this suggestion.…”
Section: Discussionmentioning
confidence: 64%
“…Several animal studies have demonstrated that vitamin D receptors are present in the parotid, submandibular and sublingual salivary glands, which suggest a possible role for vitamin D in the regulation of salivary secretion. This is supported by the finding that salivary flow rates were stimulated after treatment with vitamin D 3 in vitamin D-deficient rats (Peterfy, Tenenhouse, & Yu, 1988;Stumpf, 2008). Although the influence of vitamin D on salivary flow rate has not yet been demonstrated in humans, the finding that there was a significant positive correlation between plasma total 25(OH)D concentration and salivary flow rate in the endurance athlete cohort (N = 225) (unpublished data in our previous study (He et al, 2013), r = 0.196, P = 0.003; Pearson correlation test) might lend some support to this suggestion.…”
Section: Discussionmentioning
confidence: 64%
“…In mice, vitamin D has been shown to suppress ocular surface inflammation by inhibiting Langerhans cell migration into corneas [ 54 ], thus inhibiting corneal neovascularization [ 55 ]. Furthermore, salivary glands and their epithelial and myoepithelial cells are major vitamin D targets [ 19 ], and fluid and electrolyte secretion from the parotid gland is dependent on vitamin D directly [ 20 ]. Thus, lacrimal glands as well as corneal epithelial cells also may be affected by vitamin D. It has been reported that vitamin D deficiency is prevalent in patients with Sjogren's syndrome and that female patients with Sjogren's syndrome are at risk for vitamin D deficiency [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D is produced during exposure to sunlight, and is known to regulate calcium and phosphate homeostasis [ 10 ]. However, vitamin D receptor has been discovered in most tissues and cells in human body, including corneal epithelial cells [ 18 ], salivary glands [ 19 , 20 ], mammary glands [ 10 ], sebaceous glands [ 21 ], and immune cells [ 10 ]. Vitamin D has been suggested to play an essential role in these organs.…”
Section: Introductionmentioning
confidence: 99%
“…SIgA and cathelicidin serve as “the first line of defense” against pathogens at the mucosal surface . SIgA is an indicator of mucosal immunity, and vitamin D is involved in regulating salivary secretions . Cathelicidin is also produced at mucosal surfaces, possessing a broad range of antimicrobial activity, and its production is dependent upon sufficient vitamin D levels .…”
Section: Introductionmentioning
confidence: 99%